Evaluasi Penganggaran dalam Program Penurunan Stunting pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak DP3A Kota Surabaya - Nur Wahdatunnisa; Eva Hany Fanida; Melda Fadiyah Hidayat (Fakultas Teknik Universitas Cenderawasih, 2026)
This study aims to analyze the budgeting activities of the Surabaya City Women's Empowerment, Child Protection, and Population Control and Family Planning Agency (DP3A-PPKB) in supporting stunting reduction, while evaluating policy effectiveness, efficiency, responsiveness, and accuracy through William N. Dunn's evaluation framework. A qualitative case study design was utilized, supported by document analysis of planning records, budget realizations, and stunting prevalence data from 2019–2024. Findings reveal that DP3A's budget allocation aligns with the regional development plan and facilitates family-based sensitive interventions. Despite the first-quarter 2025 realization reaching only 9.5% of the total IDR 58.3 billion, strategic programs persisted through cross-sectoral collaboration and adaptive implementation strategies involving multiple stakeholders. The study concludes that DP3A's contributions are indirect, contingent on inter-organizational synergy among regional apparatus units (OPD). Ultimately, stunting reduction success hinges not on budget magnitude alone, but on systemic integration, policy coordination, and sustained collaborative governance across sectors. These findings emphasize the importance of strengthening institutional networks to improve program effectiveness and long-term nutritional outcomes for children.